John Thompson reading his poetry in the Hazel de Berg collection - Thompson, John, 1907-1968.; De Berg, Hazel, 1913-1984. (1960)
Thompson reads two of his poems: "Married quarrel" and "Western port".
Digital master available
Transcript available (1 p.)
Keywords: Australian poetry